EMPOWERING OF DISABLED ENTREPRENEURS THROUGH MAXIMIZATION BENEFIT OF SMALL BUSINESS LOAN - Wening Estiningsih (UNIVERSITAS INDRAPRASTA PGRI, 2014)
Disabled communities is one of the marginalized communities in the development process and policies, it also happens to disabled entrepreneurs. In the concept of empowerment, disabled entrepreneurs should be given the ease in obtaining a small business loan. This study is a conceptual paper, secondary data sourced from the literature review related to empowerment and small business loans.The aims of this study is to provide an overview the importance of the empowerment of disabled entrepreneurs through maximizing the benefits of small business loans and study is expected to be a reference for policy development related to the empowerment of disabled entrepreneurs.